2015
DOI: 10.5430/ijfr.v6n3p1
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Evidence on the Asymmetric Relationship between Bond and REIT Returns

Abstract: This paper examines the asymmetric relationship between bonds and REITs using monthly data from January 1972 through October 2014. In particular, the paper uses the nonlinear Granger causality test developed by Diks and Panchenko to underpin the dynamic interactions between bond yields and REIT returns. The results from the various unit root tests indicate that bond and REIT returns are level stationary. The results from the linear Granger causality test indicate that bond and REIT returns are not causally rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The asymmetric effects literature, for example, Balke and Fomby (1997), Kapetanios et al (2006), and Psaradakis et al (2004), emphasizes that the information conveyed by linear models is insufficient to permit a strong inference or to yield reliable forecasts (Shin et al, 2014). Anoruo and Elike (2015) highlight that the key economic variables, such as prices and real GDP, exhibit nonlinear properties. Hence, examining the asymmetric effects of the tourism elasticities offers better tourism policy guidelines compared to assuming simple linear relationships.…”
Section: Introductionmentioning
confidence: 99%
“…The asymmetric effects literature, for example, Balke and Fomby (1997), Kapetanios et al (2006), and Psaradakis et al (2004), emphasizes that the information conveyed by linear models is insufficient to permit a strong inference or to yield reliable forecasts (Shin et al, 2014). Anoruo and Elike (2015) highlight that the key economic variables, such as prices and real GDP, exhibit nonlinear properties. Hence, examining the asymmetric effects of the tourism elasticities offers better tourism policy guidelines compared to assuming simple linear relationships.…”
Section: Introductionmentioning
confidence: 99%
“…In the same vein, Gundlach confirmed this finding using a growth model, the results of which showed that human capital formation has a positive effect on output per worker twice as high as the effect of physical capital formation [4]. And Anoruo and others developed a model that supported a positive two-way causal relationship between economic growth and human capital [5]. And Siddiqui and others found that differences in growth rates between countries are attributed to differences in levels of educational progress [6].…”
Section: Literature Reviewmentioning
confidence: 76%
“…Their panel statistics have the ability to increase the power of Granger non-causality when both time and cross-sectional units are small. When cross-sectional dependence exists, this test produces unbiased results (Anoruo & Elike, 2015).…”
Section: Causality Testmentioning
confidence: 99%